High precision GPS network with precise ephemerides and earth body tide model - Monico, J. F. G. [UNESP]; Ashkenazi, V.; Moore, T. [UNESP] (Sociedade Brasileira de Geofísica, 1997)
A rede GPS do IGS (International GPS Service for Geodynamics) proporciona uma série de dados GPS global preciso, os quais são de grande valor para o desenvolvimento de algoritmos e programas computacionais para posicionamento GPS de alta precisão. A campanha intensiva denominada EPOCH '92 expandiu o núcleo da rede permitindo densificar muitas regiões do mundo. Neste projeto analisou-se os dados de uma rede brasileira com conexões para a rede global IGS. No artigo discute-se o processamento dos dados que demonstraram um nível de precisão relativa melhor que 10 ppb (partes por bilhão) para diferenças de altitudes, normalmente a pior componente. Além dos procedimentos normais do processamento de uma rede GPS, incluiu-se um modelo para Maré Terrestre.

The permanent GPS network of the International GPS Service for Geodynamics (IGS) provides a global data set of precise GPS measurements, which is invaluable in the development of algorithms and software for very high accuracy GPS positioning. The intensive EPOCH'92 campaign expanded the core network to include densification in many regions of the world. This project has involved the analysis of data from the Brazilian GPS network, with selected connections to the IGS Global Network. In this preliminary report we discuss the initial data processing, demonstrating a level of relative positioning accuracies of better than 10 ppb in height differences, typically the worst positional component. Besides the normal standard used in the processing of a GPS network, it involved an Earth body tide model.
Rede GPS de alta precisão usando efemérides precisas e modelo de maré terrestre
Keywords: GPS; Efemérides precisas; Modelo de Maré Terrestre; GPS; Precise ephemerides; Earth body tide model